Think Again Relief from the Burden of Introspection. - Mellinger, Jared (LSC-NewGrowthPress, 2017)
Stuck inside your own head? Pastor Jared Mellinger demonstrates how the hope of the gospel rescues us from too much introspection. With short, story-filled chapters and practical instructions for fighting false guilt and unhelpful self-examination, Think Again offers real relief from the burden of excessive self-analysis.